1994
DOI: 10.1111/j.1600-0749.1994.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Human Melanocytes Respond to MSH Peptides and ACTH

Abstract: Although the administration of melanocyte-stimulating hormone (MSH) peptides results in skin darkening in man, cultured human melanocytes have been reported to be unresponsive to these peptides. This may be a consequence of the conditions under which the cells were maintained in vitro, particularly the use of phorbol esters and cholera toxin as melanocyte mitogens. By culturing the cells in the absence of these additives, we demonstrate that alpha-MSH and its synthetic analogue Nle4DPhe7 alpha-MSH (NDP-MSH) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 18 publications
5
74
0
3
Order By: Relevance
“…CEFV was found to inhibit mRNA and protein levels of MITF in a dose-dependent manner, MITF is known as a major transcription factor in the regulation of tyrosinase expression, and thus plays a critical role in melanin biosynthesis. [8][9][10][11] Our results are consistent with the findings of a recent report 37) that xanthohumol (XH) significantly decreased mRNA and protein levels of MITF, suggesting that XH inhibits MITF transcription.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…CEFV was found to inhibit mRNA and protein levels of MITF in a dose-dependent manner, MITF is known as a major transcription factor in the regulation of tyrosinase expression, and thus plays a critical role in melanin biosynthesis. [8][9][10][11] Our results are consistent with the findings of a recent report 37) that xanthohumol (XH) significantly decreased mRNA and protein levels of MITF, suggesting that XH inhibits MITF transcription.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, it is well known that -MSH, as a signal transducer, potently induces MITF expression and increases melanin synthesis. [9][10][11] The extracellular signal-regulated kinase (ERK) signaling pathway plays a crucial role in cell proliferation and differentiation. 12) It has been reported that inhibition of the ERK pathway induces B16 melanoma cell differentiation and increases tyrosinase activity, suggesting that the pathway regulates melanogenesis.…”
mentioning
confidence: 99%
“…The cAMP-PKA pathway is the major signal transduction pathway involved in melanocyte-stimulating hormone receptor-mediated signaling, melanin production and melanocyte differentiation (Levine et al, 1991;Hunt et al, 1994), although its role in controlling melanocyte proliferation is still controversial. Indeed, a-melanocyte-stimulating hormone (MSH) was shown to stimulate melanocyte proliferation in vitro (De Luca et al, 1993), even if many data indicate an antiproliferative role of cAMP in these cells (Dumaz and Marais, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Of those, the most important role in the regulation of the melanocyte behavior is played by MCR1. Although there are reports showing MCR2 expression on melanocytes [46,47], its role in normal and malignant melanocytes is unclear.Concerning β-endorphin, recent reports have shown that the cutaneous β-endorphin/μ-opiate receptor system is functionally active via its ability to up-regulate melanocyte dendricity, proliferation, and pigmentation [48]. …”
mentioning
confidence: 99%